Job Analysis: A handbook for the Human Resource DirectorJob Analysis: A Handbook for the Human Resource Director, by GhorpadeJai V. Englewood Cliffs, NJ: Prentice-Hall, 1988, 342 pages, $43.67, cloth. - Graham-Moore, Brian (Academy of Management Review, 1989)
The article presents a review of the book ?Job Analysis: A Handbook for the Human Resource Director,? by Jal V. Ghorpade.